Pelatihan Technology Use - Social Media Branding for SMEs Pemilik UKM Binaan Universitas Bina Nusantara Jakarta - Siti Dewi Sri Ratna Sari; Donant Alananto Iskandar (LPMP Imperium, 2021)
The COVID-19 pandemic has drastically reduced the number of face-to-face buying and selling transactions, thus opening up opportunities for online buying and selling transactions, especially through social media. However, the owners of SMEs (Small and Medium Enterprises) do not understand how to brand their products through social media. This training activity aims to provide knowledge for SME owners assisted by Bina Nusantara University Jakarta so that they can understand social media branding to better promote their products and increase their competitiveness in the era of globalization. The method used in this activity is in the form of online training through the Zoom application with a duration of two hours which is carried out every Friday during June 2021. The training activities carried out for the participants are material explanations and case studies, followed by a question and answer session, discussion and practice. Activity participants can take part in the training well and enthusiastically, and begin to understand how to brand their products through social media. Keywords: Social media branding, UKM